Effects of metformin and pioglitazone combination on apoptosis and AMPK/mTOR signaling pathway in human anaplastic thyroid cancer cells. Issue 10 (26th June 2020) - Ozdemir Kutbay, Nilufer; Biray Avci, Cigir; Sarer Yurekli, Banu; Caliskan Kurt, Cansu; Shademan, Behrouz; Gunduz, Cumhur; Erdogan, Mehmet
Abstract: Anaplastic cancer constitutes 1% of thyroid cancers, and it is one of the most aggressive cancers. Treatment options are external radiation therapy and/or chemotherapy. The success rate with these treatment modalities is not satisfactory. We aimed to evaluate the effects of metformin (MET) and pioglitazone (PIO) combination on apoptosis and AMP‐activated protein kinase/mammalian target of rapamycin (mTOR) signaling pathway in human anaplastic thyroid cancer cells. In this study, we evaluated the effects of MET and PIO individually and the combination of the two drugs on the cellular lines SW1736 and C643 ATC. Genes contained in the mTOR signaling pathway were examined using human mTOR Signalization RT 2 Profiler PCR Array. In C643 and SW1736 cell lines, IC50 doses of MET and PIO were found out as 17.69 mM, 11.64 mM, 27.12 µM, and 23.17 µM. Also, the combination of MET and PIO was determined as an additive according to isobologram analyses. We have found the downregulation of the expression levels of oncogenic genes: AKT3, CHUK, CDC42, EIF4E, HIF1A, IKBKB, ILK, MTOR, PIK3CA, PIK3CG, PLD1, PRKCA, and RICTOR genes, in the MET and PIO combination‐treated cells. In addition, expression levels of tumor suppressor genes, DDIT4, DDIT4L, EIF4EBP1, EIF4EBP2, FKBP1A, FKBP8, GSK3B, MYO1C, PTEN, ULK1, and ULK2, were found to have increased significantly. The MET + PIO combination was first applied to thyroid cancer cells, and significant reductions in the level of oncogenic genes were detected. The decreases, particularly, in AKT3, DEPTOR, EIF4E, ILK, MTOR, PIK3C, and PRKCA expressions indicate that progression can be prevented in thyroid cancer cells and these genes could be selected as therapeutic targets.